Numerical Simulation of Chip Formation in Metal Cutting Process - ZHAO Yongjuan; PAN Yutian; HUANG Meixia (Institute of Advanced Engineering and Science, 2012)
In order to study the chip formation mechanism in metal cutting process, based on finite element software ABAQUS, establish finite element model, and carry out numerical simulation on serrated chip formation of Ni-base superalloy GH4169 and ribbon chip formation of 45# steel respectively.In addition, analyze the influence law of three factors (cutting speed, feed rate, back cutting depth) on cutting force and the distribution rule of cutting heat in serrated chip formation of GH4169.DOI: http://dx.doi.org/10.11591/telkomnika.v10i3.608